EXPLORING THE SYNERGY BETWEEN SPOKEN AND WRITTEN TEXTS: INNOVATIONS IN ENGLISH LANGUAGE TEACHING STRATEGIES - Kartika, Lusiana; Rini, Setia (VISION, 2025)
An innovative approach to harnessing this synergy is the use of multimodal learning activities. The aim of this study is to explore how the integration of spoken and written texts can support effective English language learning at various educational levels and to identify innovative strategies in English language teaching that combine spoken and written texts to enhance students' communication skills. The method used in this study is SLR (Systematic Literature Review). The result of this study is that the integration of spoken and written texts offers a rich and multifaceted approach to language learning, allowing educators to create dynamic and engaging environments that cater to the diverse needs of students.